2020
DOI: 10.1038/s41418-020-00675-x
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-dependent and -independent functions of OTULIN in cell fate control and beyond

Abstract: Ubiquitination, and its control by deubiquitinating enzymes (DUBs), mediates protein stability, function, signaling and cell fate. The ovarian tumor (OTU) family DUB OTULIN (FAM105B) exclusively cleaves linear (Met1-linked) poly-ubiquitin chains and plays important roles in auto-immunity, inflammation and infection. OTULIN regulates Met1-linked ubiquitination downstream of tumor necrosis factor receptor 1 (TNFR1), toll-like receptor (TLR) and nucleotide-binding and oligomerization domain-containing protein 2 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 82 publications
(265 reference statements)
0
23
0
Order By: Relevance
“…Moreover, we are conducting additional assays to reveal the role of RNF223 in PC, including the clinical significance of RNF223 in our collected PC samples, in vivo xenograft animal assays, and immunoprecipitation-coupled MS to identify targets of RNF223 in PC. In addition, as E3 ligases have been shown to function in both ubiquitin–proteasome-dependent and ubiquitin–proteasome-independent diseases ( Cadena et al, 2019 ; Weinelt and van Wijk, 2021 ), the specific mechanism of RNF223 in PC remains to be uncovered in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we are conducting additional assays to reveal the role of RNF223 in PC, including the clinical significance of RNF223 in our collected PC samples, in vivo xenograft animal assays, and immunoprecipitation-coupled MS to identify targets of RNF223 in PC. In addition, as E3 ligases have been shown to function in both ubiquitin–proteasome-dependent and ubiquitin–proteasome-independent diseases ( Cadena et al, 2019 ; Weinelt and van Wijk, 2021 ), the specific mechanism of RNF223 in PC remains to be uncovered in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The Glu16 side chain of the proximal ubiquitin is inserted into the active site, replacing the position of Asp336, and further restricting the His339 conformation [154]. Glu16 and Asp336 prompts His339 into an active conformation to further deprotonates Cys129 [156]. At the same time, Glu16 cooperates with Asn341 to further increase the catalytic activity of the catalytic center.…”
Section: Otulin With a Little Help Of Ubiquitin For Activationmentioning
confidence: 99%
“…OTULIN deficiency results in severe auto-inflammatory disease in patients [157]. OTULIN can protect the liver against cell death and cancer, OTULIN deficiency in non-hematopoietic cells causing liver pathology [156,158]. OTULIN inhibits liver inflammation and hepatocellular carcinoma via restraining FADD-and RIPK1 kinase-mediated hepatocyte apoptosis [159].…”
Section: Otulin With a Little Help Of Ubiquitin For Activationmentioning
confidence: 99%
“…OTULIN, which contains an OTU domain, exclusively cleaves M1-linked polyubiquitin chains. Structural studies have revealed that only the M1-linked polyubiquitin chain can exhibit optimal orientation in the catalytic triad of OTULIN [ 217 ]. OTULIN is related to inflammatory disease, which is known as OTULIN-related auto-inflammatory syndrome (ORAS).…”
Section: Dubs Regulating Diverse Rcdmentioning
confidence: 99%